Profound loss of intestinal Tregs in acutely SIV-infected neonatal macaques. Issue 2 (9th December 2014) - Wang, Xiaolei; Xu, Huanbin; Shen, Chanjuan; Alvarez, Xavier; Liu, David; Pahar, Bapi; Ratterree, Marion S; Doyle-Meyers, Lara A; Lackner, Andrew A; Veazey, Ronald S
Abstract : Marked losses of intestinal Tregs in early pediatric SIV infection may contribute to clinical gastrointestinal symptoms. Abstract: Impairment of the intestinal mucosal immune system is an early feature of HIV-infected children. Most infected children exhibit clinical gastrointestinal symptoms at some stage of infection, and persistent diarrhea is a marker for rapid disease progression. It is known that Tregs are especially important in mediating intestinal immune homeostasis and that loss of this subset may result in intestinal inflammation and associated clinical signs. Large numbers of FoxP3 + T cells were found in all tissues in newborn macaques, which coexpressed high levels of CD25 and CD4, indicating that they were Tregs . Moreover, neonates had much greater percentages of Tregs in intestinal tissues compared with peripheral lymphoid tissues. After SIV infection, a significant loss of Tregs was detected in the intestine compared with age-matched normal infants. Finally, SIV-infected FoxP3 + T cells were detected in tissues in neonates as early as 7 SIV dpi. These results demonstrate that Tregs constitute a significant fraction of CD4 + T cells in neonatal intestinal tissues and that an early, profound loss of Tregs occurs in acute SIV infection, which may contribute to the intestinal disorders associated with neonatal HIV infection.